Advances in intelligent vehicles - Chen, Yaobin; Li, Lingxi; ScienceDirect eBooks (Kidlington, Oxford, UK : Academic Press, 2014)
Advances in Intelligent Vehicles presents recent advances in intelligent vehicle technologies that enhance the safety, reliability, and performance of vehicles and vehicular networks and systems. This book provides readers with up-to-date research results and cutting-edge technologies in the area of intelligent vehicles and transportation systems. Topics covered include virtual and staged testing scenarios, collision avoidance, human factors, and modeling techniques. The Series in Intelligent Systems publishes titles that cover state-of-the-art knowledge and the latest advances in research and development in intelligent systems. Its scope includes theoretical studies, design methods, and real-world implementations and applications. Provides researchers and engineers with up-to-date research results and state-of-the art technologies in the area of intelligent vehicles and transportation systems Covers hot topics, including driver assistance systems; cooperative vehicle-highway systems; collision avoidance; pedestrian protection; image, radar and lidar signal processing; and V2V and V2I communications.
Chapter 1. Modeling and control of a new narrow vehicle -- chapter 2. Testing of intelligent vehicles using virtual environments and staged scenarios -- chapter 3. Mathematical modeling of connected vehicles -- chapter 4. Guaranteed collision avoidance with discrete observations and limited actuation -- chapter 5. Effect of human factors on driver behavior -- chapter 6. Comparative analysis and modeling of driver behavior characteristics -- chapter 7. The human factor and its handling -- chapter 8. Robust road environment perception for navigation in challenging scenarios -- chapter 9. V2I-based multi-objective driver assistance system for intersection support -- chapter 10. Letting drivers know what is going on in traffic.
Includes index.
Online resource; title from PDF title page (ScienceDirect, viewed Jan. 23, 2014).
Includes bibliographical references and index.
Elsevier
Keywords: Motor vehicles -- Automatic control; Intelligent transportation systems; Intelligent control systems; Intelligent control systems; Intelligent transportation systems; Motor vehicles -- Automatic control; Electronic books